Reflexive Personal Metadiscourse in Research Articles on Language Learning: A Discourse Analysis - Lukas Nugroho Tjioe (Universitas Gadjah Mada, 2014)
This research attempts to identify the functions of reflexive personal metadiscourse in research articles on language learning. Data for this research were taken from 17 research articles, totaling 177,309 words, published in Language Learning and Technology, an online refereed journal of language learning and technology. In total, 66 instances of reflexive personal metadiscourse were found serving 16 different functions. 93.94% of the instances commented on the on-going text, while 6.06% established interaction between the writer and the audience. The small number of occurrences of personal metadiscourse, though having various functionalities, has yet to gain considerable favor in academic writing.